2020
DOI: 10.1002/jcp.30045
|View full text |Cite
|
Sign up to set email alerts
|

A missense mutation sheds light on a novel structure–function relationship of RANKL

Abstract: The tumor necrosis factor (TNF)‐like core domain of receptor activator of nuclear factor‐κB ligand (RANKL) is a functional domain critical for osteoclast differentiation. One of the missense mutations identified in patients with osteoclast‐poor autosomal recessive osteopetrosis (ARO) is located in residue methionine 199 that is replaced with lysine (M199K) amid the TNF‐like core domain. However, the structure–function relationship of this mutation is not clear. Sequence‐based alignment revealed that the fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…To investigate whether CYT387 pre-treatment affects the transcription of NFATc1, the luciferase reporter genes were transfected into RAW 264.7 cells as previously described ( Qiu et al, 2021 ). The transfected cells were subsequently incubated in 48-well plates containing 5 × 10 4 cells/well and stimulated for 24 h using RANKL (50 ng/ml) and increasing doses of CYT387 (0.5, 1 µM).…”
Section: Methodsmentioning
confidence: 99%
“…To investigate whether CYT387 pre-treatment affects the transcription of NFATc1, the luciferase reporter genes were transfected into RAW 264.7 cells as previously described ( Qiu et al, 2021 ). The transfected cells were subsequently incubated in 48-well plates containing 5 × 10 4 cells/well and stimulated for 24 h using RANKL (50 ng/ml) and increasing doses of CYT387 (0.5, 1 µM).…”
Section: Methodsmentioning
confidence: 99%
“…RAW264.7 cell lines transfected with NF-κB, NFATc1, and ARE luciferase reporter genes were used following the previous methods ( Qiu et al, 2021 ), and these cell lines were cultured by D-MEM containing 10% FBS, 1% PS. The next day, after being treated with CAG (2.5, 5, 10 μM) for 60 min, the cells were stimulated by RANKL for stated durations, which were 6 h (NF-κB), 24 h (NFATc1), and 48 h (Nrf2/ARE).…”
Section: Methodsmentioning
confidence: 99%
“…RANKL is also a member of the TNF superfamily, and demonstrates high conservation amongst species [ 84 , 92 , 93 ]. In humans, the RANKL gene is located on chromosome 13q14, spanning approximately 36 kb of DNA [ 90 ].…”
Section: The Rank/rankl/opg System Is Influential In Bone Healthmentioning
confidence: 99%
“…Recent studies have suggested that osteocytes express high levels of RANKL in order to activate osteoclastogenesis. Knockdown models of RANKL expression in osteocytes demonstrate inhibition of osteoclast activity, increased bone density, and severe osteopetrosis [ 41 , 91 , 93 ].…”
Section: The Rank/rankl/opg System Is Influential In Bone Healthmentioning
confidence: 99%